Visions of Peru in Anthropology Peruvian (1941-2015) - Montoya Rojas, Rodrigo (2017)
A reflection is orientated on the paper of the anthropology in Peru. After a long time of the Peruvian Reality Research in the Andes, the Amazon, Lima and Villa El Salvador, and various periods of field work in Mexico, Ecuador and Bolivia. Discovering the political process of the Zapatistas in Chiapas and Political Movements indigenous in Ecuador and Bolivia, in which the established order is questioned and new horizons are offered, not only for Indigenous Peoples and our countries, also Chinese for the whole world a Fo-llowing is the vision of Peru from an anthropological reflection that can either be extended to all the Social Sciences and Humanities. It is to identify the Process, Trends and changes about the Country is expressed from anthropology.